نظرية علم النفس الديني عند زكية درجات : دراسة تحليلية في ضوء القرآن والسنة - علا، مريم قانتات متمم (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2015)
This study aims to know more about Zakiah Daradjat, as one of Indonesia's prominent women scholars who have contributed a lot to the field of education and development of Religious Psychology in Indonesia. In addition, the main purpose of this study is to analyze Zakiah Daradjat's thoughts about Religious Psychology which is her major concern. Some research on the thoughts of Zakiah Daradjat already been done by other students and researchers. But so far, no one has analyzed her thoughts on Religious Psychology from the perspective of the Qur'an and Sunnah. That is why this thesis is written as an honor, respect and appreciation of her contributions in developing Religious Psychology in Indonesia. To achieve that objective, the researcher used two main methods in this research; descriptive method and analysis method. These methods had been used by the researcher to collect all information relating to the biography of Zakiah Daradjat and her theories in Religious Psychology, which the researcher analysed according to Al-Qur'an and Sunnah perspectives. With these methods, the researcher found that Zakiah Daradjat, although did not rely directly on the verses of the Quran and Sunnah, in developing her thoughts, she does not contradict Islamic principles. For example, she argues that religious education should be given to children as early as possible for the establishment of human character with healthy mind and psyche. In addition, as the first scholar who developed Religious Psychology in Indonesia, Zakiah adjusted many Psychology terms into Islamic thought. For example, the terms 'religious attitudes in childhood', 'religious conversion', and many others. However, a few of her thoughts had some confusion with basic definitions of Islamic principles. In brief, the researcher concluded valuable findings, that the thoughts on Religious Psychology according to Zakiah Daradjat are useful if spread particularly to educational institutions as part of the establishment of human character.